1986
DOI: 10.1002/cjce.5450640203
|View full text |Cite
|
Sign up to set email alerts
|

The effect of geometric parameters on the structure of combined axial and Taylor‐Vortex flow

Abstract: The variation of Taylor‐vortex flow structure with the width of the annulus between concentric cylinders has been studied in combined axial and rotating flow by a direct visualization technique using analytical indicators. The existence of inclined wavy vortex flow with specific transition paths between several wave modes is demonstrated in the low axial Reynolds number range (0 < Re < 50).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…However, at larger Re one observes stationary spirals and mixed flow patterns [26,25] in addition to the bifurcation of propagating spirals [25,[21][22][23][24]44]. The latter are predicted by the linear stability analysis to branch off the basic state at Re ≈ 20 [19,20,52].…”
Section: Methods Of Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at larger Re one observes stationary spirals and mixed flow patterns [26,25] in addition to the bifurcation of propagating spirals [25,[21][22][23][24]44]. The latter are predicted by the linear stability analysis to branch off the basic state at Re ≈ 20 [19,20,52].…”
Section: Methods Of Investigationmentioning
confidence: 99%
“…Only for higher through-flow rates, which are not investigated here, there is a bifurcation [19,20] to spirals [20][21][22][23][24][25][26]. We have performed numerical simulations of the full, rotationally symmetric, two dimensional (2D) Navier-Stokes equations (NSE).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the narrow-gap limit, they also found that the linear theory predicts that axisymmetric vortices form that have a positive axial velocity proportional to the axial flow Reynolds number. Gu and Fahidy (1985;1986) experimentally showed that the effect of axial flow is to decrease wavelength and to increase critical Taylor number. Their range of axial flow Reynolds numbers is substantially higher than Snyder's, starting at Re,=60.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven experimentally and numerically that the vortex displacement velocity is about 1.17 times the average axial velocity. [27][28][29][30] Figure 21.14 demonstrates the stream function for different Taylor numbers in a moving frame, namely, the original velocity was subtracted by 1.17 times the average axial velocity. In Figure 21.14, the upper and lower boundaries are the outer and inner cylinders, respectively, and the vortices move from left to right.…”
Section: Effect Of Taylor Numbers On Ultraviolet (Uv) Inactivationmentioning
confidence: 99%